Kemanusiaan Yesus Kristus - Tamyong, Rospianti (Sekolah Tinggi Teologi Injili Indonesia Palu, 2024)
Discussions about the humanity of Jesus Christ today are always controversial, both in the theological and secular worlds. Humans' inability to understand and accept the fact that Jesus Christ was a true human being has resulted in rejection and refutation of this fact. However, whatever the forms of rejection of Jesus' humanity, the truth of the Bible has become accurate evidence and at the same time a definite answer to Jesus' humanity as prophesied in the Old Testament books, and supported by so many Bible verses both in the Old Testament and the Testament. New. Another interesting fact about Jesus' humanity is that He did not have a sinful nature.